ANALISIS STRATEGI PENINGKATAN PENERIMAAN PAJAK KENDARAAN BERMOTOR DALAM UPAYA OPTIMALISASI PENDAPATAN ASLI DAERAH (PAD) KABUPATEN INDRAMAYU - Rachma Aulia Putri Kurniawan; Muhammad Dahlan (CV. Denasya Smart Publisher, 2025)
This study analyzes how the strategy to increase Motor Vehicle Tax (PKB) revenue in P3DW Indramayu 1 in an effort to optimize Regional Original Income (PAD) in Indramayu Regency with a qualitative approach and descriptive analysis and using data collection techniques in the form of interviews, observations, and documentation. This research is motivated by Motor Vehicle Tax which is one of the largest sources of Regional Original Income in Indramayu Regency. The results of the study indicate that there are factors that influence the implementation of the strategy, namely regulations, human resources, facilities and infrastructure, raw material stocks, and taxpayer expectations. The strategy to be implemented is to expand collaboration with Bapenda Indramayu in response to the implementation of the Opsen PKB policy, improve facilities and infrastructure, provide creative services by carrying the tagline